2005
DOI: 10.2193/0022-541x(2005)069[1171:bsrwtr]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Biopsying Southern Right Whales: Their Reactions and Effects on Reproduction

Abstract: Collecting skin biopsies from large whales for genetic analysis is often subject to national permit, and in the case of cow‐calf pairs, it may be prohibited. We present results of 906 biopsy attempts on southern right whales (Eubalaena australis) in South African waters between 1995 and 1997, including 147 cow‐calf pairs. Our sampling success was higher for biopsy darts with a bore of 4 mm compared to 4.6 mm. Contact periods averaged 17.7 min for cow‐calf pairs and 25.4 min for whales unaccompanied by calves. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
46
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(48 citation statements)
references
References 11 publications
2
46
0
Order By: Relevance
“…Observations of reactions by large whales have shown only short-term, low-level of behavioural disturbance and no evidence of longterm impact to habitat use or reproduction (Weinrich et al 1991;Clapham & Mattila 1993;Brown et al 1994;Gauthier & Sears 1999;Hooker et al 2001;Best et al 2005;Cantor et al 2010). Observations of reactions by small cetaceans (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Observations of reactions by large whales have shown only short-term, low-level of behavioural disturbance and no evidence of longterm impact to habitat use or reproduction (Weinrich et al 1991;Clapham & Mattila 1993;Brown et al 1994;Gauthier & Sears 1999;Hooker et al 2001;Best et al 2005;Cantor et al 2010). Observations of reactions by small cetaceans (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Southern right whale (E. australis) Kato et al 1996, Patenaude et al 1998, Malik et al 2000, Best et al 2005 North Atlantic right whale (Eubalaena glacialis) Brown et al 1991, Chivers et al 2000, Malik et al 2000Brown et al 1991, Woodley et al 1991, Weisbrod et al 2000 Humpback whale (Megaptera novaeangliae) Winn et al 1973;Mathews 1986;Mathews et al 1988;Baker et al 1990Baker et al , 1993Baker et al , 1998Palsbøll et al 1995Palsbøll et al , 1997Weinrich et al 1992;Clapham and Mattila 1993;Lambertsen et al 1994;Medrano-González et al 1995;Gauthier and Sears 1999;…”
mentioning
confidence: 99%
“…Results and conclusions from these studies were first grouped and summarized to provide generalized qualitative information. Additionally, sampling rate (defined as the percentage of biopsy attempts that struck an animal and successfully retained a sample, following Best et al 2005) and percentage values for a range of behavioral response levels were calculated so that results could be quantitatively compared across studies. Several steps were taken in an attempt to standardize behavioral reactions to facilitate statistical comparison across studies.…”
mentioning
confidence: 99%
“…However, the majority of studies have shown no long-term behavioural changes to short-term impacts or injuries (Weinrich et al, 1991;Weller et al, 1997;Krützen, 2002;Best et al, 2005). Despite such a recent and extensive injury, the dolphin reported on in this study readily approached the research boat and surfed the bow wave on several occasions, including when first seen post injury.…”
mentioning
confidence: 74%